Answer:
Only for the value of x = -9 i, f(x) = g(x)
Explanation:
Here,
![f(x) = x^(2) + 9x -3 , g(x) = 9x -84](https://img.qammunity.org/2020/formulas/mathematics/middle-school/joheae9mizho8a37ckj3s5u6624k9wjq1w.png)
Now, find the values of the given functions:
A) at x = -9
![f(x) = (-9)^(2) + 9(-9) -3 = -3\\g(x) = 9(-9) - 84 = -165](https://img.qammunity.org/2020/formulas/mathematics/middle-school/8v4wcx73qt3cba4xofz9gzphp1sehcuxtz.png)
⇒ f(-9) ≠ g(-9)
B) at x = -9i
![f(x) = (-9i)^(2) + 9(-9i) -3 = -84 - 81i\\g(x) = 9(-9i) - 84 = -81i -84](https://img.qammunity.org/2020/formulas/mathematics/middle-school/r18fijjijea9cu2uf1nt43cpl1j7azjbgr.png)
⇒ f(-9i) = g(-9i)= -84 - 81i
C) at x = -3
![f(x) = (-3)^(2) + 9(-3) -3 = -26\\g(x) = 9(-3) - 84 = -111](https://img.qammunity.org/2020/formulas/mathematics/middle-school/14n1986y5jzor1u1d3uauyflazc3w3ynwc.png)
⇒ f(-3) ≠ g(-3)
D) at x = 0
![f(x) = (0)^(2) + 9(0) -3 = -3\\g(x) = 9(0) - 84 = -84](https://img.qammunity.org/2020/formulas/mathematics/middle-school/yeqifoaoom7ah0fnq2s842ogt2iaguu17w.png)
⇒ f(0) ≠ g(0)
E) at x = 9
![f(x) = (9)^(2) + 9(9) -3 = 179\\g(x) = 9(9) - 84 = -3](https://img.qammunity.org/2020/formulas/mathematics/middle-school/naz0r2vppr4ghwsea7fc380k5ms1pf960k.png)
⇒ f(9) ≠ g(9)
F) at x = 9i
![f(x) = (9i)^(2) + 9(9i) -3 = -3\\g(x) = 9(9i) - 84 = 81i -84](https://img.qammunity.org/2020/formulas/mathematics/middle-school/chszpqy8yt6kdw8q0l7u26og7gbca1cm78.png)
⇒ f(-9i) ≠ g(-9i)
Hence, only for x = -9i, f(x) = g(x)